Incentives, Team Production, Transaction Costs, and the Optimal Contract: Estimates of an Agency Model using Payroll Records - Christopher Ferrall; Bruce Shearer (Queen's University, Department of Economics, 1994)
We apply agency theory to the payroll records of a copper mine that paid a production bonus to teams of workers. As with most incentive pay used by firms, the bonus was simpler in form than the optimal contract that balances incentives, insurance, and free-riding. We explore whether transactions costs help explain this discrepancy. We estimate an agency model for the payroll data using the method of maximum likelihood and find that incentives and free-riding within teams accounted for two-thirds of the bonus system's inefficiency relative to potential full information profits. The remaining one-third of the inefficiency is attributed to the form of the incentive contract as constrained by transactions costs. We discuss alternative explanations and the general empirical content of agency theory.
Keywords: L2; D2; J3; C4; 330; principal-agent models; transactions costs; performance pay; maximum likelihood estimation